2013
DOI: 10.1149/2.028309jss
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Dissociation of Proton-Induced Donor Profiles in Silicon

Abstract: The impact of the thermal budget on the introduction and dissociation of hydrogen-related donor profiles in high purity silicon implanted with protons in the energy range of MeV is investigated. The hydrogen-related donors are radiation-induced defect complexes decorated by the implanted hydrogen. The appearance of the donor profiles is limited to the annealing temperature regime between about 350 °C and 500 °C. The activation of the doping profiles is limited by the diffusion of the implanted hydrogen from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The slope of the lines yield the activation energies and the intercepts yield the prefactors D 0 . To increase the reliability of the extracted activation energy and prefactors D 0 , additional data points were added from a very recent study from Laven et al [6] In literature, the reported diffusion coefficients of hydrogen in silicon vary over several orders of magnitude from 10 -5 to 10 -13 cm²s -1 . Activation energies of hydrogen in silicon, extracted by experimental measurements, are reported from 0.48 eV [8] to 1.2 eV [9][10][11].…”
Section: Resultsmentioning
confidence: 99%
“…The slope of the lines yield the activation energies and the intercepts yield the prefactors D 0 . To increase the reliability of the extracted activation energy and prefactors D 0 , additional data points were added from a very recent study from Laven et al [6] In literature, the reported diffusion coefficients of hydrogen in silicon vary over several orders of magnitude from 10 -5 to 10 -13 cm²s -1 . Activation energies of hydrogen in silicon, extracted by experimental measurements, are reported from 0.48 eV [8] to 1.2 eV [9][10][11].…”
Section: Resultsmentioning
confidence: 99%
“…H + implantations in the dose range of 10 13 -10 15 H + /cm² and anneals in the temperature range from 350 °C to 550 °C are used to form H-related thermal donor complexes [2,11]. The concentration and type of these thermal donors strongly depend on the annealing temperature and annealing time [12][13][14][15][16] the formation and dissociation process of these donor complexes was investigated in various studies using deep level transient spectroscopy [17], infra-red spectroscopy [18], electron paramagnetic resonance [19] and spreading resistance profiling [20]. One important application of H + implantation doping is as a field stop of an Isolated Gate Bipolar Transistor (IGBT) [8].…”
Section: Introduction Because Protons (H +mentioning
confidence: 99%
“…Alternative fabrication methods have been tested, where the formation of ntype columns was realized via the implantation of hydrogen ions [4,5]. Although the formation of deep doping profiles due to the implantation of hydrogen [6] is a very useful method, this process is not used because the formation/dissociation [7] and diffusion processes [8] of the hydrogen-related thermal donors are still not well understood and may lead to reliability issues. …”
mentioning
confidence: 99%